A erosão do espaço público: uma cartografia da desafetação das áreas públicas municipais em Goiânia, entre 1954 a 2016 - Souza, Maria Ester de (2019)
Public space is the very reason the city exists. The production and appropriation of this urban space reflects the human culture materialized in cities, in any historical time and in any territory. The thesis starts from the premise that public space, even outside the context in which it is formally created - urban laws - is a territory of dispute between the agents involved in the production of urban space. In the normative context, the public space, named Municipal Public Area, becomes a financial asset for public management through a legal process called disaffection. The Law on Disaffection allows the change of public destination of immovable property, making it, according to the literature of law, alienable, and can be donated, transferred, loaned or sold by the government. Despite being an expedient of the legal system, provided for in the urban legislation, the process of disaffection takes on a political character in the constitution of a city when it reveals the use of the land of the APMs by the real estate agents and politicians, for the formation of a stock of land for commercialization, contrary to the same legislation that states that urban planning should be guided to the social function of the city and property. It turns out that, in the tradition of the formation of Brazilian cities, urban land has always been understood as heritage, a monopoly of the few. It is possible to identify in the city of Goiânia, a stock of land little known by the set of inhabitants of the city. These are lands scattered throughout the urban space that, generally because they are not built or urbanized for public use, are confused with private areas. This action is functional for the real estate market that bets on the invisibility of APMs as a strategy to increase its monopoly and thus maintain control over city planning. To demonstrate this hypothesis, from the methodological point of view, an evolutionary cartography of the disaffection was elaborated. From the survey of the laws published in the Official Gazette of the City of Goiânia, from 1954 to 2016, disaffected APMs (donated or sold) were cataloged and analyzed from a periodization in three phases. In addition, the survey of the urban regulatory framework in the capital contributed to the data analysis. The maps reveal the erosion process of the public space in the capital of Goiás and how this process remains regular, that is, laws of public areas disruption are being published daily, precarious urban space